Fabrication of planar microcoils for LC-MEMS pressure sensor - Norliana, Yusof; Badariah, Bais; Norhayati, Soin; Muhamad Ramdzan, Buyong; Burhanuddin, Yeop (2020)
This paper addresses the design and fabrication of a small scale planar microcoil for LC-MEMS pressure sensor application. A simple process flow based on MEMS fabrication is presented and the key aspects of the processing are discussed. The fabricated microcoils were characterized both morphologically and electrically. The characterizations performed on the fabricated microcoils showed that the aluminum traces from end to end contact displayed good connection with high conductivity. The inductance, resistance and quality factor (Q-factor) value of microcoils were measured at 2.49 uH, 58.4 U and 0.27, respectively at a 1 MHz operating frequency. The square planar microcoil was successfully fabricated and is applicable for future LC-MEMS pressure sensor application.